Mass Spectral Fragmentation Modes of Chromon-6-yl Alkanoic Acids and Esters - Prabha Sharma, Vinay; V. Singh, Om (Asian Journal of Chemistry, 2010)
Mass spectral fragmentation modes of chromon-6-yl alkanoic acids and their esters are being reported in this paper which have shown a definite pattern of fragmentation.